Volume 3: Gas Turbine Heat Transfer; Transport Phenomena in Materials Processing and Manufacturing; Heat Transfer in Electronic 2013
DOI: 10.1115/ht2013-17738
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Design Optimization of Multi-Floor, Counterflow Micro Heat Exchangers

Abstract: Heat removal capacity, coolant pumping pressure drop and surface temperature non-uniformity are three major challenges facing single-phase flow microchannel compact heat exchangers. In this paper multi-objective optimization has been performed to increase heat removal capacity, and decrease pressure drop and temperature non-uniformity in single-flow microchannels. Three-dimensional (3D) 4-floor branching networks have been applied to increase heat removal capacity of a microchannel from silicon substrate (15×1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Multi-objective Genetic Algorithm II (NSGA-II) developed by Deb et al [24,25], was chosen to perform optimization. The four simultaneous objectives of the optimization study were: 1) Maximize total heat removed, 2) Minimize total pressure drop, 3) Minimize temperature non-uniformity on hot surface 4) Minimize temperature on hot surface Abdoli and Dulikravich [14] demonstrated that Gaussian Radial Basis Function (GRBF) method gives more accurate results in comparison to other response surface methods. Then, this GRBF was coupled to NSGA-II multi-objective optimization algorithm in modeFRONTIER software in order to perform the optimization.…”
Section: Multi-objective Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-objective Genetic Algorithm II (NSGA-II) developed by Deb et al [24,25], was chosen to perform optimization. The four simultaneous objectives of the optimization study were: 1) Maximize total heat removed, 2) Minimize total pressure drop, 3) Minimize temperature non-uniformity on hot surface 4) Minimize temperature on hot surface Abdoli and Dulikravich [14] demonstrated that Gaussian Radial Basis Function (GRBF) method gives more accurate results in comparison to other response surface methods. Then, this GRBF was coupled to NSGA-II multi-objective optimization algorithm in modeFRONTIER software in order to perform the optimization.…”
Section: Multi-objective Optimizationmentioning
confidence: 99%
“…Husain and Kim [13] performed single objective optimization using response surface approximation in order to find optimal microchannel width, depth, and fin width. Abdoli and Dulikravich [14] performed multi objective optimization for 4-floor branching microchannel configurations with 67 design variables in order to improve heat removal and decrease temperature nonuniformity and coolant pumping pressure drop. There is still a need for more research on single-phase flow microchannels in order to increase heat transfer efficiency and decrease temperature non-uniformity and pressure drop [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous optimization work, Jelisavcic et al [6] and Gonzales et al [7] found an optimum configuration of network of cooling passages. Abdoli and Dulikravich [8,9,10,11] also optimized multi-floor microchannel configurations. Fabbri and Dhir [12] optimized an array of microjet for cooling of high performance electronics.…”
Section: Introductionmentioning
confidence: 99%